2017
DOI: 10.3847/1538-4357/aa5f56
|View full text |Cite
|
Sign up to set email alerts
|

Mass Distribution in Galaxy Cluster Cores

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 137 publications
(273 reference statements)
13
64
1
Order By: Relevance
“…Hogan et al (2017) developed techniques to determine cluster mass profiles across wide radial ranges that extend from cluster halos into the cores of the central galaxies. We adopt this methodology in this paper to calculate more accurate t cool /t ff profiles for a large sample of clusters, many of which are actively experiencing thermally unstable cooling.…”
Section: Review Of T Cool /T Ff Models and Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hogan et al (2017) developed techniques to determine cluster mass profiles across wide radial ranges that extend from cluster halos into the cores of the central galaxies. We adopt this methodology in this paper to calculate more accurate t cool /t ff profiles for a large sample of clusters, many of which are actively experiencing thermally unstable cooling.…”
Section: Review Of T Cool /T Ff Models and Observationsmentioning
confidence: 99%
“…Furthermore the t cool /t ff minimum is usually reported to occur at cluster-centric radii of 5-20kpc (e.g., Gaspari et al 2012;Hogan et al 2017). Highresolution measurements are therefore required to constrain the minimum value of t cool /t ff .…”
Section: Mass Samplementioning
confidence: 99%
See 2 more Smart Citations
“…This deviation may indicate a transition from the potential of the BCG to that of the Fornax Cluster. Hogan et al (2017) also found § For an annular sector, we calculate its volume as V = . For a box region, we assume it is a cylinder in 3D with an approximately radial symmetry axis and we calculate its volume as V = l × π(w/2) 2 .…”
Section: A Quasi-isothermal Potentialmentioning
confidence: 99%